Military Spending and Innovation: Learning from 19th Century World Fair Exhibition Data - Alexander M. Danzer; Natalia Danzer; Carsten Feuerbaum (Center for Economic Studies and ifo Institute (CESifo), 2023)
We provide quantitative evidence on the relationship between military spending and innovation in the 19th century. Combining innovation data from world fairs and historical military data across Europe, we show that national military spending is associated with national innovation towards war logistics such as food processing, but less towards war technology such as guns. This pattern reflects differences in the historical markets for war supplies. European patent data of 1990-2015 suggest a long-term correlation between historical and contemporaneous innovation patterns.
Keywords: H56; O31; O14; N43; 330; military spending; innovation; war logistics; food processing; military supply; 19th century